Vitamin D in corticosteroid-naïve and corticosteroid-treated Duchenne muscular dystrophy: what dose achieves optimal 25(OH) vitamin D levels?. Issue 10 (31st May 2016) - Alshaikh, Nahla; Brunklaus, Andreas; Davis, Tracey; Robb, Stephanie A; Quinlivan, Ros; Munot, Pinki; Sarkozy, Anna; Muntoni, Francesco; Manzur, Adnan Y
Abstract : Aim: Assessment of the efficacy of vitamin D replenishment and maintenance doses required to attain optimal levels in boys with Duchenne muscular dystrophy (DMD). Method: 25(OH)-vitamin D levels and concurrent vitamin D dosage were collected from retrospective case-note review of boys with DMD at the Dubowitz Neuromuscular Centre. Vitamin D levels were stratified as deficient at <25 nmol/L, insufficient at 25–49 nmol/L, adequate at 50–75 nmol/L and optimal at >75 nmol/L. Result: 617 vitamin D samples were available from 197 boys (range 2–18 years)—69% from individuals on corticosteroids. Vitamin D-naïve boys (154 samples) showed deficiency in 28%, insufficiency in 42%, adequate levels in 24% and optimal levels in 6%. The vitamin D-supplemented group (463 samples) was tested while on different maintenance/replenishment doses. Three-month replenishment of daily 3000 IU (23 samples) or 6000 IU (37 samples) achieved optimal levels in 52% and 84%, respectively. 182 samples taken on 400 IU revealed deficiency in 19 (10%), insufficiency in 84 (47%), adequate levels in 67 (37%) and optimal levels in 11 (6%). 97 samples taken on 800 IU showed deficiency in 2 (2%), insufficiency in 17 (17%), adequate levels in 56 (58%) and optimal levels in 22 (23%). 81 samples were on 1000 IU and 14 samples on 1500 IU, with optimal levels in 35 (43%) and 9 (64%), respectively. No toxic level was seen (highest level 230 nmol/L). Conclusions: The prevalence of vitamin D deficiency and insufficiency in DMD is high. A 2-month replenishment regimen of 6000 IU and maintenance regimen of 1000–1500 IU/day was associated with optimal vitamin D levels. These data have important implications for optimising vitamin D dosing in DMD.